ANALYSIS OF BURNOUT IN NON-UNIVERSITY PROFESSORS IN THE REGION OF MURCIA (SPAIN) DEPENDING ON THE TYPE OF SCHOOL: PUBLIC VERSUS PRIVATE - Latorre Reviriego, Isabel; Sáez Carreras, Juan (Anales de Psicología / Annals of Psychology, 2009)
The burnout is an emotional and mental illness that appears in professions with human interactions. The objective of this study was to analyze the influence of the type of school at the onset of burnout. We de-signed a cross-sectional study by filling in questionnaires in a population of 200 teachers from non-university levels. As variables were measured, depending on the type of school: epidemiological data, stress level and consequences, and burnout by the Maslach Burnout Inventory. The epide-miological results have shown significant differences in age, seniority and job stress level (p < .05), being the sex, marital status, number of children and emotions similar in both groups. The level of burnout has been the same regardless of the type of center. Our study has shown that a profes-sor at a public shows less support in 5 areas: amount of support, valua-tion, motivation, emotional support and satisfaction. No differences in the area of support heard. Regarding collective, the support received from students makes the difference between teachers in both types of centers, remain a constant in each of the areas discussed. The support of groups of friends, family and parents is the same for all teachers, regardless of the center. In conclusion, the type of school affects the level of stress and so-cial support received by the teacher, although the level of burnout is the same. Preventive measures are needed to prevent this disease and bridge the gap between centres trabajo.